THE CULINARY POTENTIAL OF THE ARCHIPELAGO AS TOURISM DEVELOPMENT WITH A HISTORICAL REVIEW OF CASE STUDIES YOGYAKARTA AND BANYUWANGI - Soetopo, Dhalia; Wulandari, Nuryuana Dwi (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
The development of the world of tourism after the Covid-19 pandemic provides opportunities for the development of tourism products. This study aims to determine the potential of traditional food in Yogyakarta as tourism development; To find out the potential of traditional food in Banyuwangi. This study uses a descriptive qualitative research method with data collection techniques in the form of interviews with sources, documentation, and supported by literature. The results of this study indicate that 1) Yogyakarta as a tourist city has many menus that can be used to attract tourists including gudeg, bakpia, ingkung, tiwul and Gatot, stir fry mercon, 2) traditional food menus that can be used to attract tourists including botok wasp, uceng-uceng, lanun, pepes olin, and kelemben. These traditional food menus are inseparable from the history of the first time these menus existed and were served. Based on the discussion that has been conveyed by the researchers, it can be concluded that traditional food influences tourists to visit an area, it is necessary to have a good relationship between the government, the community and tourists. If regional tourism is developed, the economy of the community around the tourist object will also feel a positive impact.